Depositor discipline in Russian regions: Flight to familiarity or trust in local authorities? - Koen Schoors; Maria Semenova; Andrey Zubanov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
We analyze whether a depositor's familiarity with a bank affects depositor behavior during a financial crisis. Familiarity is measured by the presence of regional or local cues in the bank's name, while depositor behavior is considered in terms of depositor sensitivity to observable bank risk (market discipline exerted by depositors). Using the 2001–2010 bank-level and region-level data for Russia, we show the evidence that depositors use quantity-based discipline on all banks in the sample. The evidence of a price-based discipline mechanism, however, is virtually absent. We find that depositors of familiar banks were less sensitive to bank risk after a financial crisis than depositors at unfamiliar banks. To assure the results are driven by familiarity bias and not implicit support of regional governments to banks with regional cues in their names, we interact the variables with measures of trust in local governments and regional affinity. We find a "flight to familiarity" effect strongly present in regions with strong regional affinity, while the effect is rejected in regions with greater trust in regional and local governments. This suggests that the results are driven by familiarity rather than implicit protection from trusted regional or local governments.
URN:NBN:fi:bof-201701251055
Keywords: G21; G01; P2; 330